The Position and Nature of the Philosophy of Science - Emi Nuraemi; Maspuroh; Erna Robiatul Adawiah; Muhammad Nursyauqi (Bibliotheca: Journal of Philosophy, 2025)
Philosophy occopies a central position in science and is the basis for in-depth thinking about nature, methods and rationality of science. Philosophy contributes to the development of science by helping formulate new theories and evaluating the validity of existing knowledge. In addition, philosophy can reduce misunderstandings and provide moral guidance in decision making. The aim of this research is to determine the status and essence of the philosophy of scince, including the meaning, objectives, research objects and status of the philosophy of science, as well as approaches, ways of working, foundations, essence, aims, values and meaning. From the philosophy of sciene. The research method used is the documentary research research method, namely collecting data from books, journals, articles and certain works. Philosophy has a long history in the history of  science. Philosophy is older than science and most religions. Knowledge begins with curiosity, certainty with doubt, and philosophy with both. We encourage philosophical thinking to find  out what we already know and what we never know in a seemingly infinite universe. Likewise, philosophizing means introspection and self-correction, the courage to be honest about how far the truth we seek has actually been achieved.